EDITORIAL (Brazilian Geographical Journal, 2012)
The editorial process of the Brazilian Geographical Journal (BGJournal) was evaluated from its inception in 2010 until present. Currently the journal is indexed by various important index database from Latin America, United States and Europe. During 2010, 2011 and 2012 (January-June) 39, 47 and 25 manuscripts were received. The average time of publication was four mouths. The average rate of rejection was 20%, and 70 articles were published from 2010 to present, from 15 Brazilian states, and 11 countries published in English, Portuguese, Spanish and French languages. Brazilian Agency CAPES evaluated in the journal in the 2010-2011 triennium as Qualis B- 3 in Geography, B-4 Engineering I and B-5 Engineering III and Biodiversity. The journal is fulfilling its mission and its objectives in the areas of Geosciences and Humanities.